Implementation Of Relaxation Therapy Listening To Music In Hypertensive Patients - Sahrudin, Udin (Universitas Pendidikan Indonesia, 2024)
Background : Hypertension causes the aorta and large arteries to reduce their ability to accommodate the volume of blood pumped by the heart, resulting in a decrease in heart rate. To overcome a decrease in cardiac output, this is by providing classical music therapy. Objective: This study aims to find out the description of nursing care for patients with reduced cardiovascular function and hypertension with the implementation of music listening therapy. Methods: This research was conducted using a case study. Results: The results of the assessment showed that the client said he had a history of hypertension, felt headache, shoulder and leg pain, was worried about his illness, and tired quickly. A nursing diagnosis of acute pain, ineffective health care and obesity was obtained. The intervention is by providing music therapy and health education. Conclusion: After carrying out these actions, the results showed that the problem of pain and health maintenance, while the problem of obesity was partially resolved. The evaluation results showed blood pressure in the range of 130/90 mmHg.